The Glass Ceiling Phenomenon Revisited - Danton, Mathew; Maniam, Balasundram; Subramaniam, Geetha (International Journal of Engineering and Technology, 2018)
Although the number of women entering the workforce has continuously increased, women still find themselves lower than men on the corporate ladder. This study explores the effects of the metaphorical glass ceiling and the professional advancement of women over the past century. It will look at what women and organizations can do to try to eliminate the glass ceiling phenomenon. Lastly, the study looks at how the glass ceiling has changed over time and if it is still relevant today?Â